Fantastic Submotives in the Martyrium of St. Perpetua and St. Felicita - Petkov, Angel (Forum Theologicum Sardicense, 2025)
Angel Petkov, Miraculous Submotives in the Martyrium of St Perperua and Felicitas. The Martydom of Saints Perpetua and Felicity (Passio Sanctorum Acta Perpetuae et Felicitatis) recounts the final days of a group of North African Christians in the 2nd century. This narrative has been extensively studied by scholars specializing in ancient martyr literature. A notable feature of the text is the visions experienced by Perpetua and Satur while in prison. These visions are vivid and reveal divine messages through fantastic imagery. This style of writing martyrdom acts is innovative and bears similarities to the contemporary sci-fi genre. Using Arthur C. Clarke’s novel 2001: A Space Odyssey as a model, we examine how classic science fiction features are reflected in the Martyrdom of Saints Perpetua and Felicity. The first feature is the high realism in the descriptions, characterized by detailed portrayals of mystical scenes and objects. The second feature is adherence to scientific knowledge. The third feature involves addressing contemporary public concerns. The fourth feature is the vast unknown, which is present in both works and prompts readers to ponder the issues and themes raised. The ancient genre of Aretology likely serves as the literary framework for the text, as it shares common elements with "The Life of Apollonius of Tyana".